Knowledge, attitude, practices and associated factors of family planning among women living with hiv at the university of Gondar specialized hospital: a cross sectional study - Wudneh Simegn; Eman Hussen; Yossef Maru; Abdulwase Mohammed Seid; Liknaw Workie Limenh; Wondim Ayenew; Mihret Melese; Berhanemeskel Weldegerima Atsbeha (BMC, 2024)
Abstract Introduction HIV/AIDS poses a significant health challenge in sub-Saharan African countries, with a disproportionate impact on women of reproductive age. The disparities in knowledge, attitudes, and practices related to family planning among women living with HIV can be intricate and multi-faceted. This study aimed to assess the knowledge, attitude, practice, and associated factors regarding family planning among the women living with HIV at the University of Gondar specialized hospital, Gondar, Ethiopia. Method A cross-sectional study was carried out at the University of Gondar Teaching Referral Hospital, focusing on HIV-positive women of reproductive age who visited the ART unit from July 8-28, 2022. Data collection involved the use of pre-tested, structured questionnaires administered through interviews. The gathered data were entered into the electronic Kobo Collect platform and subsequently exported for analysis using SPSS version 26. Descriptive summaries, including frequencies, means, and percentages, were presented through tables and figures. Logistic regression was employed to identify potential predictors, presenting adjusted odds ratios with a 95% confidence interval and a significance level set at a P-value of 0.05. Results A total of 328 study participants were included. About 93% of the study population had good knowledge about modern contraceptives, and about 94% of the study population had good knowledge about safer conception. Only 30.2% of the study population had knowledge of the dual contraceptive method. The attitude and practice of women towards family planning (FP) were 71.0% and 55.8%, respectively. The study revealed that the most commonly employed contraceptive method was injectable contraceptives, constituting 34.2% of usage. Having one and a greater number of children (AOR = 2.25, 95% CI: 1.10, 4.49), having discussions on fertility plans with healthcare providers (AOR = 2.20, 95% CI: 1.02, 4.761), and having good family planning practices (AOR = 2.15, 95% CI: 1.19, 3.87) were significantly associated with the attitude toward family planning. Married women (AOR = 1.88, 95% CI = 1.11, 3.1), able to read and write (AOR = 2.12, 95% CI:1.04,4.32), college and above educational level (AOR = 4.51, 95% CI:1.93,10.87), had discussion on fertility plan with healthcare providers (AOR = 5.09, 95% CI: 1.96, 13.24), knowledge about dual method (AOR = 1.95, CI: 1.08, 3.50), and knowledge about modern contraceptive methods (AOR = 7.24, 95% CI: 1.56, 33.58) were significantly associated with good practice of family planning. Conclusion Women living with HIV exhibited notably high levels of knowledge regarding modern contraceptive methods and safer conception. The knowledge of the dual method was low. More than half of the study population had good practice in family planning. More than two-thirds of HIV-positive reproductive-age women had a good attitude about family planning. Having one or a greater number of children, having a discussion on a fertility plan with a healthcare provider, and having a good practice of family planning were significantly associated with a good attitude toward family planning. Married women, education status, discussions on fertility plans with healthcare providers, knowledge about dual methods, and knowledge about modern contraceptive methods were significantly associated with good family planning practices. The stakeholders should design interventions based on the aforementioned factors to improve the attitude and practice of family planning.